Trans-regional Influences and the Modern-Traditional Character of Nahdlatul Ulama in Contemporary Indonesia - Ghafur, Muhammad Fakhry; Mashad, Dhurorudin; Basyar, M. Hamdan (Journal of Posthumanism, 2025)
Nahdlatul Ulama (NU), the largest Islamic organisation in Indonesia, historically has been associated with rural-based traditionalism. Nevertheless, recent developments indicate a discernible ideological shift towards a modern-traditional synthesis. The article employs a critical juncture framework to investigate the trans-regional dynamics that have shaped NU’s evolving identity. The study resulted in three key findings. Firstly, it is evident that NU’s traditionalist foundations have, since its inception, been influenced by trans-regional Islamic thought. This has served to challenge the static view of its traditionalism. Secondly, the process of globalization, which has been accelerated by technological advancements and cross-border exchanges, has intensified the impact of these external influences. Thirdly, the increasing prevalence of nationally educated NU cadres, many of whom have pursued their studies at international institutions, has led to the integration of trans-regional discourses within the leadership and intellectual framework of the NU. These individuals have played a pivotal role in redefining the organisation’s ideological trajectory, forging a modern-traditional character that reflects both continuity and transformation within Indonesian Islam.